2015
DOI: 10.1021/acs.jpca.5b01347
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of NCN: Shock-Tube Study, Quantum Chemical Calculations, and Master-Equation Modeling

Abstract: The thermal decomposition of cyanonitrene, NCN, was studied behind reflected shock waves in the temperature range 1790-2960 K at pressures near 1 and near 4 bar. Highly diluted mixtures of NCN 3 in argon were shock-heated to produce NCN, and concentration-time profiles of C atoms as reaction product were monitored with atomic resonance absorption spectroscopy at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…the literature, which is in excellent agreement with our work, was concerned with the unimolecular decomposition of NCN using the C-ARAS technique [8,9]. So far, no experimental high-temperature rate constant measurements have been performed for the reaction with molecular oxygen…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…the literature, which is in excellent agreement with our work, was concerned with the unimolecular decomposition of NCN using the C-ARAS technique [8,9]. So far, no experimental high-temperature rate constant measurements have been performed for the reaction with molecular oxygen…”
Section: Introductionsupporting
confidence: 87%
“…These studies include the reactions NCN + NO, NO 2 , NCN + NCN, O, and M as well as NCN + H and NCN + H 2 . The only other direct study reported in the literature, which is in excellent agreement with our work, was concerned with the unimolecular decomposition of NCN using the C‐ARAS technique . So far, no experimental high‐temperature rate constant measurements have been performed for the reaction with molecular oxygentrueright NCN +O2 products .…”
Section: Introductionsupporting
confidence: 78%
“…The entire experiment was controlled by a home-written computer program. NCN 3 was synthesized by the reaction of NaN 3 (purity: 99%) with BrCN (97%) [45,46] in analogy to the procedure described earlier [5,9]. First, pestled NaN 3 was filled in a 30 cm Vigreux column and fixed with glass wool.…”
Section: Methodsmentioning
confidence: 99%
“…In combustion chemistry, the kinetics of the cyanonitrene radical, NCN, has recently attracted attention [4][5][6][7][8][9][10][11] because NCN is considered an important intermediate in the formation of so-called prompt NO in hydrocarbon flames under fuel-rich conditions [12][13][14][15][16][17][18][19][20]. Cyanonitrene is a linear diradical with a 3 − g electronic ground state [21,22] and was shown to be formed under combustion conditions in the spin-allowed reaction CH(…”
Section: Introductionmentioning
confidence: 99%
“…45,46 For more details of our specific implementation see ref. [47][48][49] and the literature cited therein.…”
Section: Statistical Rate Theory Calculations and Master Equation Anamentioning
confidence: 99%